Pemisahan Kewenangan Kepala Daerah dalam Menjalankan Pemerintahan dengan Pemegang Saham BUMD - Suwandi, Dedy; Abib , Agus Saiful; Tamba, Tumanda (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
The implementation of local government which is the authority of regional heads in the implementation of State Administration is certainly very Administrative, but keep in mind that regional heads also have the authority to create regional owned enterprises or BUMD for short. The authority possessed by the regional head, namely the administrative authority with the business policy of the two regulations, is certainly very different both in terms of policy and accountability. It should be borne in mind that these two powers should not be mixed so that there is a need for a ban on the restriction of authority owned by the regional head.. In reviewing this article normative juridical approach is expected to find the other side of the extent to which the policy of legal norms to see the objective position in the separation of powers between the head of government administration policy with business policy as a shareholder of BUMD. The division of authority should be separated between the administrative authority of the government, with local governments as shareholders in this case the majority vote in the GMs, and should not only be limited to government regulations because according to the author BUMD is a Lex specialist in a company the arrangement should be specifically in the form of legislation so that there are checks and balances with the House of Representatives.